METODE PENGUKURAN ENERGI GELOMBANG PASANG SURUT BERDASARKAN REKAMAN CITRA TIMELAPSED PERMUKAAN FLUIDA - Setiawan, Dewa Gede Eka ([Yogyakarta] : Universitas Gadjah Mada, 2012)
A method on measurement of a tidal wave energy based on time lapsed image recording of the surface of fluid has been carried out. Experimental simulation has been developed using pumped water flow that was controlled by a solenoid valve. The water was passed through a transparent tube in which the surface of the fluid as a representation of the tidal wave can be examined using a CCD camera. The frequency of the tidal wave was resulted from open-close frequency of the solenoid. As the open-close frequency of the solenoid was run, a tidal change as a function of time can be examined using a time lapsed image recording method. The tidal pattern was developed based on the images recorded. The tidal pattern was then compared by pattern resulted from lagrange formulation. The pattern resulted from simulation was similar to the pattern resulted from lagrange formulation. The results of the experiment showed that the physical quantities such as the period of oscillation, frequency, amplitude and speed of wave can be calculated to yield the tidal energy. The tidal wave energy of the fluid surface as a variation of frequency for solenoid valve 4Hz, 2Hz and 0,67Hz yield wave energy of 3.25x10-2 Joules, 15.33x10-2 Joules and 198.24x10-2 Joules respectively. Assuming the open-close solenoid was proportional to the frequency of the tidal oscillation, then it was concluded that the frequency of tidal wave affects the resulting of energy. The lower the frequency, the higher the tidal wave energy.